Interconnections between BDH1-plasma protein-type 2 diabetes Mellitus: a mediated mendelian randomization analysis using plasma proteomics - Yi-Ying Liu; Yue-Yang Zhang; Qin Wan (Scientific Reports)
Abstract With the rapid advancement of proteomics, numerous scholars have investigated the intricate relationships between plasma proteins and various diseases. Therefore, this study aims to elucidate the relationship between BDH1 and type 2 diabetes using Mendelian randomization (MR) and to identify novel targets for the prevention and treatment of type 2 diabetes through proteomics. This study primarily employed the Mendelian Randomization (MR) method, leveraging genetic data from numerous large-scale, publicly accessible genome-wide association studies (GWAS). Within this framework, we adopted a two-step, two-sample MR approach to evaluate the relationships between BDH1, plasma proteins, and type 2 diabetes. Finally, we conducted bidirectional MR analyses along with various sensitivity analyses to ensure the robustness and reliability of the study findings. The inverse variance weighted (IVW) analysis demonstrated that for each 1 standard deviation (SD) increase in BDH1, the risk of type 2 diabetes decreased by 3% (OR: 0.97; 95% CI: 0.95, 0.99). Concurrently, the proteomics-based MR analysis identified 37 plasma proteins associated with type 2 diabetes and 27 plasma proteins associated with BDH1. Notably, NBN, ARG1, and CCL11 were found to mediate the protective effect of BDH1 on type 2 diabetes. Our research findings uncovered the potential protective effect of BDH1 on type 2 diabetes and identified several plasma proteins associated with the disease. These results open new avenues for enhanced exploration of the prevention and treatment of type 2 diabetes.